ANALISIS PERHITUNGAN, PEMOTONGAN, PELAPORAN, dan PENYETORAN PAJAK PENGHASILAN (PPh) PASAL 21 ATAS KARYAWAN TETAP (Studi Kasus Pada PT. Sarah Ratu Samudera) - Anggraini, Dian (Jurnal Mahasiswa Perpajakan, 2014)
PT. Sarah Ratu Samudera is a company that concern on forwading sector in Surabaya. PT. Sarah Ratu Samudera withholding Income Tax Article 21 every month over the employee. Problems experienced by the company often incorrectly calculating and reporting and late payment of Income Tax Article 21 payable. This research was conducted in PT. Sarah Ratu Samudera Surabaya. This study was conducted to see how the calculation mechanism, withholding, payment and reporting of Income Tax Article 21 above the regular employees using withholding tax system. The study was conducted by using descriptive methods and data collection technique using documentation and interviews. Calculation of Income Tax Article 21 PT. Sarah Sarah Samudera for income received on a regular full-time employees is correct, but PT. Sarah Ratu Samudera does not count the number of Income tax Article 21 for irregular income received by employees in, named THR. Mistakes made by the company in calculating Income Tax Article 21 payable in August and December 2013 will result the amount of taxes paid and reported not as it should be. Article 21 are paid and reported smaller. Keywords: Withholding of Income tax Article 21, Payment, Reporting